خیر و شر کے نظریاتی و عملی مظاہر: متکلمین و مفسرین کے آراء کا تقابلی مطالعہ: Theoretical and Practical Manifestations of Good and Evil: A Comparative Study of Theologians and Exegetes' Views - Dr. Syeda Ayisha Rizvi; Muhammad Idrees; Dr. Barkat Ullah Khan Qureshi (International Research Journal of Arabic and Islamic Studies, 2024)
The theoretical and practical manifestations of good and evil constitute a vast and intricate subject in Islamic theology. This paper aims to explore these manifestations through a comparative study of the views of Islamic theologians and exegetes. The primary focus is on understanding not only the theoretical aspects of good but also its practical implications as prescribed by the Quran. The concept of good is presented as more than a mere theoretical construct; it is intended to guide individuals towards practical application. The discussion includes the role of destiny (qadar) in human actions, a fundamental belief in Islam that is both delicate and significant. It is crucial to balance the divine creation of human actions with the concept of human autonomy, ensuring that the notions of command, prohibition, and divine justice are preserved. The paper reviews key Islamic works on destiny, including those by Imam Abu Bakr al-Firabi, Imam Ibn Taymiyyah, Imam Ibn Qayyim, Imam Muhammad ibn Salih al-Uthaymin, and Imam Umar ibn Sulayman al-Ashqar. By analyzing these texts, the paper aims to provide a comprehensive understanding of how good and evil are conceptualized within Islamic thought. It is divided into six sections: introduction, the meaning of destiny, the obligation of faith in destiny, types of actions, views on good and evil, and a summary.